2022
DOI: 10.3389/fonc.2022.833486
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognostic Analysis of 55 Patients With Pulmonary Sarcomatoid Carcinoma

Abstract: Pulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive subtype of non-small-cell lung cancer (NSCLC). Here, we present information on the clinicopathologic characteristics and clinical outcomes of this type of cancer. Clinicopathologic data from 55 patients treated at a single cancer center from January 2011 to December 2018 were retrospectively analyzed. The patients were mostly male (76.4%), with a median age of 66 years and a history of smoking (54.5%). Most had symptoms, and about 60% presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In addition, they elucidated that the TNM stage, especially T staging and M staging, was associated with the prognosis of PSC. These data were consistent with previous studies ( 4 , 6 , 7 ).…”
supporting
confidence: 94%
“…In addition, they elucidated that the TNM stage, especially T staging and M staging, was associated with the prognosis of PSC. These data were consistent with previous studies ( 4 , 6 , 7 ).…”
supporting
confidence: 94%
“…Pulmonary sarcomatoid carcinoma (PSC) is a rare subset of non-small-cell lung cancer (NSCLC), characterized by poorly differentiated tumors with a component of sarcoma or sarcomalike elements 1 and highly aggressive biological behaviors. [2][3][4][5] PSC has been reported to be associated with poor prognosis and low responsiveness to first-line chemotherapy, with an objective response rate (ORR) of 16.5% and overall survival (OS) of only 6.3 months. 6 Therefore, developing novel therapeutic strategies to improve the dismal prognosis of patients with this malignance is in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the presence of mediastinal lymph node metastasis has been correlated with an increased risk of distant metastasis and reduced overall survival. These findings underscore the importance of early detection and accurate staging of lymph node involvement in the management of PSC (21,22). Zhao et al ( 23) demonstrated a higher prevalence of smoking history in patients with PSC and its close association with poor prognosis.…”
Section: Discussionmentioning
confidence: 82%